A BTB-TAZ protein is required for gene activation by Cauliflower mosaic virus 35S multimerized enhancers. Issue 1 (27th September 2021) - Irigoyen, Sonia; Ramasamy, Manikandan; Misra, Anjali; McKnight, Thomas D; Mandadi, Kranthi K
Abstract: The Arabidopsis ( Arabidopsis thaliana ) B TB-T AZ DOMAIN PROTEIN 2 (BT2) contains an N-terminal BTB domain, a central TAZ zinc-finger protein–protein interaction domain, and a C-terminal calmodulin-binding domain. We previously demonstrated that BT2 regulates telomerase activity and mediates multiple responses to nutrients, hormones, and abiotic stresses in Arabidopsis. Here, we describe the essential role of BT2 in activation of genes by multimerized Cauliflower mosaic virus 35S ( 35S ) enhancers. Loss of BT2 function in several well-characterized 35S enhancer activation-tagged lines resulted in suppression of the activation phenotypes. Suppression of the phenotypes was associated with decreased transcript abundance of the tagged genes. Nuclear run-on assays, mRNA decay studies, and bisulfite sequencing revealed that BT2 is required to maintain the transcriptionally active state of the multimerized 35S enhancers, and lack of BT2 leads to hypermethylation of the 35S enhancers. The TAZ domain and the Ca ++ /calmodulin-binding domain of BT2 are critical for its function and 35S enhancer activity. We further demonstrate that BT2 requires CULLIN3 and two bromodomain-containing G lobal T ranscription factor group E proteins (GTE9 and GTE11), to regulate 35S enhancer activity. We propose that the BT2-CULLIN3 ubiquitin ligase, through interactions with GTE9 and GTE11, regulates 35S enhancer activity in Arabidopsis. Abstract : Activation of gene expression by the multimerized Cauliflower mosaic virus 35S enhancers requires the function of a putative BTB-TAZ ubiquitin ligase.